THE EFFECT OF TAX KNOWLEDGE, TAX DISSEMINATION AND MODERNIZATION OF THE TAX ADMINISTRATION SYSTEM ON TAXPAYER COMPLIANCE (CASE STUDY OF BANDENG PRESTO MSMES REGISTERED IN THE IUMK SEMARANG CITY) - Candra Safitri; Agung Budiarto; Ahmad Sahri Romadon (SEAN Institute, 2023)
Tax is one of the components with the largest contribution to the revenue of the State Revenue and Expenditure Budget (APBN), the budget is needed in the context of national development. The community during national development has grown Medium, Small and Micro Enterprises (MSMEs) with 61.07% a tax revenue contribution. In the Semarang city there are 17,603 MSMEs registered in the IUMK. Bandeng Presto is one of the products processed by UMKM which is a special food the Semarang city. There are various problems encountered in achieving the realization of tax revenues. Tax compliance is a serious problem for most developing countries because it reduces the state's ability to collect taxes there by reducing the country's ability to carry out development. There are many factors that cause of taxpayer compliance, especially for Bandeng Presto SMEs, namely Tax Knowledge, Tax Socialization and Modernization of the Tax Administration system. This study aims to examine the effect of Tax Knowledge, Tax Socialization and Modernization of the Tax Administration system on Taxpayer Compliance in MSMEs Bandeng Presto. The population in this study were Bandeng Presto SMEs registered in the IUMK with a total of 159 SMEs, sample selection was based on convenience sampling and size determination using the Slovin formula, resulted in a sample of 61 respondents. The data collection survey method with questionnaires as a data collection tool. The analysis technique used is data quality test (Validity, Reliability), Classical Assumption Test (Multicollinearity Test, Heteroscedasticity Test, Normality Test), Model Feasibility Test, (Coefficient of Determination, F Test), Hypothesis test, and Multiple Linear Regression Analysis Test. The results of this study are Tax Knowledge and Tax Administration System Modernization have a positive and significant effect on Taxpayer Compliance, while Tax Socialization has no effect on Taxpayer Compliance.